Molecular stratification of medulloblastoma: comparison of histological and genetic methods to detect Wnt activated tumours - Goschzik, Tobias; Pfister, Stefan (Neuropathology & applied neurobiology, 2015)
AIMS: Wnt activation in medulloblastomas is associated with good outcome. Upfront testing and risk-adapted stratification of patients will be done in future clinical studies. In a cohort of 186 paediatric medulloblastomas our aim was to identify the optimal methods in standard clinical practice to detect this subgroup. METHODS: Nuclear accumulation of β-catenin was analysed by immunohistochemistry (IHC). DNA of FFPE tissue was amplified by PCR for single-strand conformation polymorphism analysis and direct sequencing of CTNNB1 exon 3. Copy number of chromosome 6 was analysed by multiplex ligation-dependent probe amplification and molecular inversion profiling.RESULTS: Different automated immunostaining systems showed similar results. Twenty-one of 186 samples had nuclear accumulation in ≥5% of cells, 17 samples showed <5% β-catenin positive nuclei. None of these 17 cases had CTNNB1 mutations, but 18 of 21 cases with ≥5% accumulation did, identifying these 18 cases as Wnt-subgroup medulloblastomas. Fifteen of 18 mutated cases showed monosomy 6, 3 had balanced chromosome 6. On the contrary, none of the CTNNB1 wild-type tumours had monosomy 6. CONCLUSIONS: Standard neuropathological evaluation of medulloblastoma samples should include IHC of β-catenin because tumours with high nuclear accumulation of β-catenin most probably belong to the Wnt subgroup of medulloblastomas. Still, IHC alone may be insufficient to detect all Wnt cases. Similarly, chromosome 6 aberrations were not present in all CTNNB1-mutated cases. Therefore, we conclude that sequencing analysis of CTNNB1 exon 3 in combination with β-catenin IHC (possibly as pre-screening method) is a feasible and cost-efficient way for the determination of Wnt medulloblastomas.